2010
DOI: 10.1007/s12310-010-9043-4
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of Non-Suicidal Self-Injury in the Schools

Abstract: Non-suicidal self-injury (NSSI) is a growing concern among professionals working with youth. The present study investigated the self-reported confidence, knowledge, and attitudes regarding NSSI among 155 high school teachers (51 men, 104 women). More than half of the teachers (60%) responded that they found the idea of NSSI ''horrifying.'' When asked about their own levels of confidence in dealing with NSSI, 67% said that they would feel comfortable if a student spoke to them about NSSI; however, only 43% felt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 37 publications
6
86
1
7
Order By: Relevance
“…This lack of training in the area of self-harm was perceived to impact negatively on their confidence in responding to students who self-harmed which is a finding mirrored in other studies (Simm, Roen & Daiches, 2010;Heath et al 2011;Berger et al 2014b). The newly published Irish suicide prevention strategy has recommended suicide and self-harm training and awareness programmes for those who come into regular contact with people who are vulnerable to self-harm or suicidal behaviour (Department of Health, 2015).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This lack of training in the area of self-harm was perceived to impact negatively on their confidence in responding to students who self-harmed which is a finding mirrored in other studies (Simm, Roen & Daiches, 2010;Heath et al 2011;Berger et al 2014b). The newly published Irish suicide prevention strategy has recommended suicide and self-harm training and awareness programmes for those who come into regular contact with people who are vulnerable to self-harm or suicidal behaviour (Department of Health, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…A lack of knowledge about self-harm and self-cutting in particular and a requirement for further training was also identified by Carlson, DeGeer, Deur,& Fenton (2005) in a quantitative study of 150 teachers in the United States (US). The majority of teachers in a Canadian study by (Heath, Toste, Sornberger & Wagner, 2011) identified that they would feel comfortable if a student spoke to them about self-injury yet less than half (43%) actually felt knowledgeable about this behaviour indicating a deficit between willingness to help and ability to offer effective counsel. The lack of education and training in the area of self-harm is not limited to teachers as evidenced by findings relating to school counsellors in the US (Roberts-Dobie & Donatelle, 2007) and Canada (Duggan, Heath, Toste & Ross, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Negative attitudes not only dissuade individuals from seeking help but also lead to the withholding of helping behaviors (Heath et al, 2011;Owens et al, 2016).…”
Section: Public Attitudes and Helpingmentioning
confidence: 99%
“…Further, there is some evidence that affective responses and personal responsibility beliefs are related to behavior responding in teaching professionals (Heath et al, 2011) and prison staff (Marzano et al, 2015). However, there is a dearth of research exploring factors influencing "general population" perceptions of self-harm.…”
Section: Current Studymentioning
confidence: 99%
“…Studies have demonstrated that the behaviour is very prevalent among adolescents (Muehlenkamp & Gutierrez, 2004;Ross & Heath, 2002), and researchers attempting to identify the etiology of NSSI have identified that one of the main functions of NSSI is as a mechanism for reducing strong negative emotions (e.g., Klonsky, 2009). However, North American and international studies have found prevalence rates generally ranging from 14% to 20% among adolescents, with some studies reporting up to 39% (for a review, Heath, Schaub, Holly, & Nixon, 2008) and school professionals report that NSSI behaviour is increasing among high school students (Heath, Toste, & Beettam, 2006;Heath, Toste, Sornberger, & Wagner, 2011). Adolescents who engage in NSSI most commonly report an age of onset ranging from 12 to 14 years, during middle and high school (Rodham & Hawton, 2009).…”
mentioning
confidence: 99%